Re(a)d wedding: A case study exploring everyday information behaviors of the transmedia fan. Issue 1 (24th October 2017) - Forcier, Eric
ABSTRACT: As practitioners of new forms of consumption and production, fans represent an important area for research. Specifically, fans of "transmedia systems" – media‐hopping networks of intertextualities that extend the narrative world of an original production – employ unique tactics for negotiating a complex information space. The study of such tactics provides valuable insights on the everyday information behaviors of modern post‐digital readers and media consumers that could benefit literacy and community engagement. Despite this, fans have received little attention in the information behavior literature. Therefore, this paper seeks to contribute new empirical understandings of the transmedia fan to the information behavior domain. The author undertook a pilot case study of the Game of Thrones transmedia fandom. Using a grounded theory approach, the qualitative coding of 400 online user comments revealed four types of tactics employed by fans to negotiate the transmedia system: sentimental, reasoned, relational and comic. A discussion of these tactics and the ways in which fans use them results in a preliminary definition and information behavior cycle model for the transmedia fan . The study's findings offer key observations about the everyday information behavior of fans and about reading and media consumption practices in general.